Relevance of Cognition and Emotion for Patient-Reported Quality of Life After Stroke in Working Age: An Observational Cohort Study - Pinter, Daniela; Fandler-Höfler, Simon; Fruhwirth, Viktoria; Berger, Lisa; Bachmaier, Gerhard; Horner, Susanna; Eppinger, Sebastian; Kneihsl, Markus; Enzinger, Christian; Gattringer, Thomas (Frontiers in Neurology, 2022)
Background: Patient-reported quality of life (QoL) may help to more comprehensively capture sequela of stroke. We aimed to investigate QoL in working age ischemic stroke patients regarding impaired domains and identify factors associated with better QoL. Methods: We invited stroke patients aged 18-55 years to participate in this prospective observational study. We assessed QoL using the EuroQol 5 Dimension questionnaire (EQ-5D) during hospital stay (baseline) and at three-months follow-up (FU). Additionally, National Institute of Health Stroke Scale (NIHSS), modified Rankin Scale (mRS), cognition (Montreal Cognitive assessment, MOCA), emotion (Hospital Anxiety and Depression Scale) and return to work were evaluated. We used hierarchical regression to identify predictors of QoL (self-rated health and QoL Index score) at FU. Results: We included 138 patients (mean age=43.6±10 years; 41% female; median admission NIHSS=2), of whom 99 participated at FU. QoL Index and self-rated health correlated with NIHSS, mRS, anxiety and depression at both timepoints. Although, 80% had favorable functional outcome at FU (mRS<2), high proportions of these patients reported problems in the dimensions “Pain and/or Discomfort” (25.3%) and “Anxiety/Depression” (22.8%). Only discharge NIHSS and baseline MOCA independently predicted self-rated health at FU. Female sex, higher discharge NIHSS and higher baseline depression scores predicted worse QoL Index scores at FU. Conclusions: Three months post-stroke, working age patients frequently reported problems in dimensions not assessed by the routinely used mRS. Despite correlations between clinical scales and QoL, patient-reported outcomes and screening for cognition and emotion ensure a more comprehensive assessment of post-stroke consequences relevant for QoL.